Effects of Season on Ignition of Live Wildland Fuels Using the Forced Ignition and Flame Spread Test Apparatus. Issue 2 (1st February 2017) - McAllister, S.; Weise, D. R.
ABSTRACT: An understanding of what variables affect the ignition of live wildland fuels is crucial to predicting crown fire spread, the most poorly understood type of wildland fire. Ignition tests were performed over the course of an entire year for ten species (three species in year one, seven in year two) to evaluate seasonal changes in flammability. Ignition delay and mass loss rate at ignition were measured for a radiant heat flux of 50 kW/m 2 and flow velocity of 1 m/s. Large species-to-species variation occurred in two-variable linear correlations between moisture content, ignition time, and mass loss rate at ignition. Only a few species showed the same behavior as wet wood. Due to potential physical and chemical changes that live fuels undergo during the growing season, moisture content is not a particularly useful descriptor of ignition behavior for live fuels.